DIAGNOSIS OF MYELOMA BASED ON THE 2014 INTERNATIONAL MYELOMA WORKING GROUP - Maitri Febrianthi; Riadi Wirawan (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2018)
Myeloma is a cytogenetically heterogenous clonal plasma cells proliferative disorder and is almost always preceded by an asymptomatic premalignant stage termed monoclonal Gammopathy of Undetermined Significance (MGUS). Diagnosis of myeloma is based on International Myeloma Working Group (IMWG) 2003 which requires one or more CRAB features including hypercalcemia, renal insufficiency, anemia and lytic bone lesions. The IMWG 2014 updated criteria for the diagnosis of myeloma allows the use of early indicators for therapy before CRAB features happen. This is a case of a 53-year-old male, based on complete blood count and peripheral blood smear having normochromic normocytic anemia, NRBC 7/100 leucocytes, thrombocytopenia, 1% plasmoblasts, 11% plasmocytes and Erythrocyte Sedimentation Rate (ESR) 40 mm. The bone marrow evaluation showed plasmocytes 22.5% ANC with abnormal morphology. The diagnosis myeloma was made based on IMWG 2014 by the presence of plasmocytes 22.5% ANC the bone marrow and having one of Myeloma Defining Events (MDEs) in the form of anemia with hemoglobin level 8.5 g/dL. In addition, patient did examinations of protein electrophoresis, immunofixation and ratio involved/uninvolved Free Light Chain (FLC) serum. The results of those examination confirmed the diagnosis that has been made based on IMWG 2014. Prognosis of the patient is poor by the presence of 11% plasmocytes on blood peripheral and ratio FLC kappa/lambda 0.0010.